The Influence of Meteorological Variables on Air Pollutants Improvement using Hibiscus Cannabinus L. Kenaf Filter - Suryati, Sulaiman; Noor Suraya, Romali; Abdul Syukor, Abd Razak; Rokiah, Othman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Bauxite mining activities has led to serious consequences towards humans and environment in term of water pollution, air pollution and has extensively damaged the ecosystem of aquatic life. This study investigates the performance of Hibiscus Cannabinus L. (Kenaf) fibres in improving air pollutants. The influence of meteorological conditions i.e. temperature and wind speed, as well as the thickness of Kenaf fibre filter on the concentration of PM10, NH3, NO2 , and Cl2 after the Kenaf fiber treatment is established. The bauxite sample was collected near Kuantan Port, Pahang and a prototype was fabricated to test ability of the Kenaf fibres in improving air quality. Wind speed and temperature was modified to be similar as the actual conditions on site. The study found that the Kenaf fibre filter improved the concentration of PM10, NH3, NO2 , and Cl2 efficiently after air treatment. Two layers of Kenaf fiber filter showed better performance in removing air pollutants as compared to one-layer filter. One-layer filter is capable to improve 16% to 43% of PM10, NH3, NO2 , andCl2 concentration, whereas as high as 70% of pollutants can be removed when two-layer filter is utilized. The removal efficiencies of NH3 , NO2 , Cl2 and PM10 (with Kenaf) increased from 33%, 17%, 38% and 75% to 60%, 67%, 73% and 85% respectively when the wind speed increased from 900 rpm to 1200 rpm. In contrast, the percentages of removal decreased when higher temperature was applied. The removal of PM10, NH3, NO2 , andCl2 decreased from 75%, 60%, 69% and 41% to 57%, 50%, 65% and 39% respectively when the temperature was increased from 27 °C to 32 °C.